2002
DOI: 10.1093/aje/kwf074
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Alzheimer's Disease: A Prospective Analysis from the Canadian Study of Health and Aging

Abstract: A prospective analysis of risk factors for Alzheimer's disease was a major objective of the Canadian Study of Health and Aging, a nationwide, population-based study. Of 6,434 eligible subjects aged 65 years or older in 1991, 4,615 were alive in 1996 and participated in the follow-up study. All participants were cognitively normal in 1991 when they completed a risk factor questionnaire. Their cognitive status was reassessed 5 years later by using a similar two-phase procedure, including a screening interview, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
760
9
43

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,125 publications
(853 citation statements)
references
References 35 publications
41
760
9
43
Order By: Relevance
“…The aetiology of sporadic AD is not well known, but several risk factors have been shown to increase the probability of developing the disease 3 . Although the main risk factor for AD is aging, various others factors have also been proposed, including gender, ApoE polymorphism, the coexistence of other disorders (such as cardiovascular diseases, brain injury, diabetes and Down syndrome) and several lifestyle conditions, including physical activity, education, diet or smoking 4,5 .…”
mentioning
confidence: 99%
“…The aetiology of sporadic AD is not well known, but several risk factors have been shown to increase the probability of developing the disease 3 . Although the main risk factor for AD is aging, various others factors have also been proposed, including gender, ApoE polymorphism, the coexistence of other disorders (such as cardiovascular diseases, brain injury, diabetes and Down syndrome) and several lifestyle conditions, including physical activity, education, diet or smoking 4,5 .…”
mentioning
confidence: 99%
“…When the ApoE4 allele was present, the HR was below 1.00 only for light drinkers, and above 1.00 for heavier drinkers ( Several other prospective studies have reported an association between alcohol consumption and dementia. A Canadian study (6) reported that at least weekly consumption of alcohol was associated with a decreased risk of Alzheimer's disease (OR=0.68, [0.47-1.00].…”
mentioning
confidence: 99%
“…An especially interesting finding was that education, well known to be associated with higher risk of dementia [28] and AD, [18,21,41,47] was not associated with any of the AD lesion groups. This supports data from the Nun Study indicating that educational attainment was not related to fulfillment of neuropathologic criteria for AD.…”
Section: Discussionmentioning
confidence: 93%